A self-assembling luminescent lanthanide molecular nanoparticle with potential for live cell imaging. Issue 20 (2nd May 2018) - Yang, Xiaoping; Wang, Shiqing; Zhang, Yali; Liang, Guang; Zhu, Ting; Zhang, Lijie; Huang, Shaoming; Schipper, Desmond; Jones, Richard A.
Abstract : A 32-metal Cd–Tb nanocluster with enhanced visible luminescence was constructed by the introduction of energy transfer donors (1, 4-BDC) for potential bioimaging applications. Abstract : Four luminescent 32-metal Cd–Tb nanoclusters, [Tb8 Cd24 (L 1 )12 (OAc)48 ] (1 ), [Tb8 Cd24 (L 2 )12 (OAc)48 ] (2 ), [Tb8 Cd24 (L 3 )12 (OAc)48 ] (3 ) and [Tb8 Cd24 (L 2 )12 (1, 4-BDC)4 (OAc)38 (OH)2 ] (4 ), were constructed from three specially designed chain-like Schiff base ligands H2 L 1–3 with flexible carbon–carbon backbones containing 5, 6 and 10 methylene units, respectively. The clusters exhibit drum-like structures and can be imaged using transmission electron microscopy (TEM). In addition to the Schiff base ligands (the primary energy transfer donors), four 1, 4-BDC bridging units were successfully introduced into the structure of4 . In addition to providing increased structural stability, the 1, 4-BDC units act as secondary energy transfer donors providing extra energy for lanthanide luminescence, which results in improved luminescence properties when compared to those of the related Cd–Ln nanoclusters without 1, 4-BDC units. In vitro investigations on4 with SGC and PANC cancer cells revealed an accumulation of the molecular nanoparticles in the cells, as confirmed by confocal microscopy. The cytotoxicity of4 toward the SGC and PANC cells is moderate (IC50 values of4 lie in the range of 15–60 μM). ICP-MS analysis reveals that cellular uptakes of4 in 1000 SGC and PANC cells after treatment for 3 hours are 0.0094 pmol and 0.015 pmol, respectively.